Hard currency and sound credit: A financial agenda for Central Europe - Rudi Dornbusch; Francesco Giavazzi (EIB Papers, 1999)
This paper argues that Central Europe should draw the lessons from the Asian and Mexican crises: hard money and sound credit are essential in a world where capital is intensely mobile, contagion pervasive and the economic and social costs of crises nothing short of formidable. We argue that Central European countries should adopt a currency board using the euro as their reference currency. In this part of the world a currency board system is eminently plausible because trade patterns link the region closely to the markets of the European Union. Moreover, the appearance of the euro, in conjunction with the intense desire of the East to become integrated in the European market, removes the traditional nationalist objections to a currency board. The argument for moving now is opportunity. Europe is in the midst of a historic transformation that affords governments with an absolutely unique opportunity to do those things which ordinarily are politically impossible.
Keywords: 330; Currency Board; Euro; Osteuropa